Geographic isolation and environmental heterogeneity shape population genetic differentiation of a medicinal plant, amla (Phyllanthus emblica L.) in river valleys of Yunnan, China - Wang, Cai-yun; Huang, Jia-cong; Yin, Ming-yu; Hu, Hong-jiang; Yang, Yan-ping; Guo, Jun-jie; Zeng, Jie (Frontiers in Plant Science, 2025)
The diverse topographies of high mountains and deep river valleys in Yunnan, China create geographic and environmental barriers that promote intraspecific genetic differentiation. This study employed amla (Phyllanthus emblica L.) to reveal the effects of geographic and environmental isolation on genetic differentiation of plant species. We sampled 18 natural P. emblica populations from upstream to downstream in the Longchuan, Nu, Lancang, Yuanjiang and Jinsha Rivers valleys (three or four per valley) in 2017. Genetic diversity and structure of P. emblica were assessed across these populations using 16 SSR loci developed, and analyzed with GenAlEx, ATetra, and STRUCTURE software packages. Ecological niche modeling (MaxEnt) estimated its historical and contemporary potential geographic distribution patterns, and redundancy analysis (RDA) identified key environmental factors influencing genetic diversity. P. emblica exhibited high genetic diversity, primarily influenced by mean temperature of the warmest quarter (Bio10) and precipitation of the warmest quarter (Bio18). STRUCTURE analysis revealed a distinct division of these populations into western and eastern groups, closely aligned with the Tanaka-Kaiyong Line. Significant genetic differentiation existed between the western and eastern populations, and suggesting that long-term geographic isolation and environmental heterogeneity promote genetic differentiation and local adaptation of this species. MaxEnt modelling indicated a significant expansion in the potential habitat of P. emblica from the Last Glacial Maximum (LGM) to the present, likely due to climate warming. Our findings provide evidence for genetic differentiation in P. emblica driven by geographical and environmental isolation, and offer critical insights into developing effective conservation and utilization strategies for its genetic resources.